2009
DOI: 10.1007/s10593-009-0365-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on 5-(2-aryl-2-oxo-ethylidene)-1,3-dimethylbarbituric and thiobarbituric acids: reactions with thioureas and thioacetamide

Abstract: Keywords: 5-(2-amino-4-arylthiazol-5-yl)-6-hydroxy-2-thioxo-2,3-dihydropyrimidin-4(1H)-ones, 5-(2-amino-4-arylthiazol-5-yl)-1,3-dimethylpyrimidine-2,4-diones, 5-(2-aryl-2-oxoethylidene)-1,3-dimethylbarbituric and 5-(2-aryl-2-oxoethylidene)thiobarbituric acids, thioacetamide, thioureas, one-pot synthesis, cyclocondensation.It is well known that heterocyclization involving α,β-unsaturated ketones and thioureas is a convenient method of synthesis of 3,4-dihydropyrimidine-2-thiones [1-3]. However an alternative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Kolos et al reported the reaction of thioureas and thioacetamide with 317 , which were obtained by Knoevenagel condensation of 136 with AGs. The thioureas or thioacetamide were treated with 317 in refluxing EtOH or MeOH and the corresponding 2-aminothiazoles 319 or 2-methylthiazoles 318 were obtained in 45–76% or 37–56% yields, respectively (Scheme ).…”
Section: Synthesis Of Five-membered Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kolos et al reported the reaction of thioureas and thioacetamide with 317 , which were obtained by Knoevenagel condensation of 136 with AGs. The thioureas or thioacetamide were treated with 317 in refluxing EtOH or MeOH and the corresponding 2-aminothiazoles 319 or 2-methylthiazoles 318 were obtained in 45–76% or 37–56% yields, respectively (Scheme ).…”
Section: Synthesis Of Five-membered Heterocyclesmentioning
confidence: 99%
“…383 Many reports have appeared in the literature describing the formation of benzothiazoles, 384 including condensation reaction of o-aminothiophenol with carboxylic acid derivatives or aldehyde followed by oxidation 384h−j and intramolecular cyclization of thioanilides. 384f,k−o Kolos et al 385 reported the reaction of thioureas and thioacetamide with 317, which were obtained by Knoevenagel condensation of 136 with AGs. The thioureas or thioacetamide were treated with 317 in refluxing EtOH or MeOH and the corresponding 2-aminothiazoles 319 or 2-methylthiazoles 318 were obtained in 45−76% or 37−56% yields, respectively (Scheme 92).…”
Section: Synthesis Of Five-membered Heterocyclesmentioning
confidence: 99%
“…The process starts with the condensation of 8 and 5 into Knoevenagel adduct C followed by an aza-Michael addition of 7 and an intramolecular aza-condensation involving glyoxal-originated carbonyl group. The approach is based on a number of mechanistically similar transformations utilizing N , N -, N , C -, and N , S -bis-nucleophiles that were developed in the last decades for the diversity-oriented synthesis (DOS) of heterocycles. In the current investigation, we attempted to utilize HKAs 1 in a similar three-component reaction with aryl glyoxals 8 and cyclic 1,3-dicarbonyl compounds 5 paying particular attention to the possibility of attaining different heterocyclic cores by diverting the mode of the final aza-cyclization step through the substrate-controlled chemoselectivity (Scheme d).…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Kolos and co-workers described a modification of this process using dimethyl barbituric acid 6a instead of ß-ketoester 3 , providing access to imidazol-2-ones of type 7b (Scheme c) . Later the Kolos group expanded this chemistry to the use of thiourea and thioacetamide as urea replacements and to the use of 4-hydroxycoumarin as a 1,3-dicarbonyl compound . In 2010, Quiroga, Nogueras and co-workers further contributed to this area with the three-component reaction of 6-aminopyrimidine 8 , aryl glyoxal 5 , and dimedone 6b for the synthesis of various pyrrolo­[2,3- d ]­pyrimidines 9 .…”
Section: Introductionmentioning
confidence: 99%